Clinical characteristics, trichoscopy, histopathology and treatment outcomes of frontal fibrosing alopecia in an Asian population: A retro‐prospective cohort study. Issue 11 (24th July 2020) - Panchaprateep, Ratchathorn; Ruxrungtham, Pariya; Chancheewa, Bussabong; Asawanonda, Pravit
Abstract: Frontal fibrosing alopecia (FFA) is a distinctive lymphocytic scarring alopecia with rapid increase in prevalence. Most FFA series are retrospectively reported from Caucasians with only few from Asians. The objective of this study was to characterize the clinical, trichoscopic and histopathological findings as well as treatment outcomes. This was a retro‐prospective cohort study of patients diagnosed with FFA from 1 January 2010 to 1 November 2019. All patients were asked to present for re‐examination. Clinical, trichoscopic, histopathological and laboratory data were recorded. A questionnaire was used to investigate hair care, hairstyle and facial skin care compared with age‐matched normal controls. Multivariate analysis was performed in order to clarify factors associated with severity. All 58 FFA patients were female, of whom 27.6% were premenopausal, 37.7% had a history of surgical menopause, 13.8% had thyroid diseases, 69% had eyebrow loss and 32.8% facial papules. On physical examination, 10.3% showed linear pattern, 46.6% diffuse pattern and 43.1% pseudo‐fringe sign. Concomitant lichen planopilaris was found in 25.9%, lichen planus pigmentosus in 24.1% and female pattern hair loss in 48.3%. The most common trichoscopic characteristics in the frontal hairline were lack of follicular ostia (91.4%), perifollicular scales (79.3%) and perifollicular erythema (63.8%). Up to 90% of patients reported FFA as improved or stable after receiving antiandrogen (finasteride or dutasteride) or antimalarial with topical treatment. Multivariate analyses revealed that facial lentiginous macules and trichoscopic perifollicular erythema at the frontal area were FFA severity‐associated factors. "Front puff" Thai hairstyle was associated with FFA, while sunscreens and other cosmetic products were not. In conclusion, diffuse and pseudo‐fringe sign pattern are common in Asian FFA. The most common autoimmune systemic comorbidity is thyroid disease, while common concomitant dermatological diseases are female pattern hair loss, lichen planopilaris and lichen planus pigmentosus. Antiandrogens or antimalarial plus topical treatment are the most useful therapy.